2013
DOI: 10.1016/j.phrs.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib enhances antigen-specific cytotoxic T cell responses against immune-resistant cancer cells generated by STAT3-ablated dendritic cells

Abstract: Dendritic cell (DC)-based vaccines have received attention as a new therapeutic modality against cancer. However, increased STAT3 activity in the tumor microenvironment makes DCs tolerogenic and suppresses their antitumor activity. In this study, we explored the effects of a combination treatment consisting of a proteasome inhibitor, bortezomib, and an antigen specific STAT3-ablated (STAT3−/−) DC-based vaccine on the control of TC-1(P3) tumors, a p53-degraded immune resistant cancer cells. We found that E7-ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Most important, deletion of STAT3 in DCs did not improve the efficacy of prophylactic or therapeutic DC vaccination in the GL26 mouse tumor model. A recent publication similarly showed that STAT3 knock down in DCs elicited no improvement in in-vivo therapeutic efficacy of monotherapy vaccination in a TC-1 murine cervical cancer model when used by itself [27] . Improved survival using STAT3 knock down DC vaccination was elicited when used in combination with bortezomib treatment via a CD8 + T cell response [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Most important, deletion of STAT3 in DCs did not improve the efficacy of prophylactic or therapeutic DC vaccination in the GL26 mouse tumor model. A recent publication similarly showed that STAT3 knock down in DCs elicited no improvement in in-vivo therapeutic efficacy of monotherapy vaccination in a TC-1 murine cervical cancer model when used by itself [27] . Improved survival using STAT3 knock down DC vaccination was elicited when used in combination with bortezomib treatment via a CD8 + T cell response [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib enhanced Ag-specific cytotoxic T-cell responses against immune-resistant cancer cells generated by STAT3-ablated DCs [27]. Also, bortezomib could restore MART-1 Ag expression on human melanoma cells to sensitize them to specific CTLs in vitro [28].…”
Section: Host Responsiveness To Bortezomib Treatmentmentioning
confidence: 99%
“…BTZ treatment can lead to immunogenic cell death in MM cells, resulting in uptake by, and contact-dependent activation of DC through, exposure of heat shock proteins [8]. Given that BTZ can enhance the efficacy of tumor vaccination [8,33], these findings have prompted several groups to study the effects of BTZ on functional DC development and maturation. Thus far, the majority of reports have described the effects of short-term exposure to BTZ on MoDC, an in vitro model of inflammatory DC development, and without exception, have shown deleterious effects on DC maturation, most notably through BTZ-mediated inhibition of proteasomal chymotrypsin activity [10][11][12].…”
Section: Discussionmentioning
confidence: 99%